SOCIAL INJUSTICE TOWARD THE CROSSDRESSER IN ROBERT GALBRAITH’S TROUBLED BLOOD - Wening , Cornelia Tyas; Dewi, Novita (Fakultas Hukum dan Sosial Humaniora Universitas Flores, 2024)
This research aims to determine the problems of social injustice experienced by crossdressers—in the form of discrimination and stigma or stereotypes—in the novel Troubled Blood by J.K. Rowling, who uses the pseudonym Robert Galbraith. This research was conducted using qualitative descriptive methods. Meanwhile, the theories used are several theories related to gender, such as gender theory itself, queer theory, and crossdressing theory. Apart from that, identity and social justice theories are also used to analyze acts of social injustice related to the identity of crossdressers in society. The book Gender Trouble by Judith Butler is also a supporting reference regarding social views that shape gender identity, thereby causing limitations for non-binary groups. The results of this research show that the character Dennis Creed in the novel Troubled Blood by Robert Galbraith represents the social injustice received by crossdressers, as well as the real impact for crossdressers and other non-binary groups from the depiction of crossdressers as criminals in several novels.